Toward regeneration of articular cartilage. Issue 3 (23rd September 2013) - Iwamoto, Masahiro; Ohta, Yoichi; Larmour, Colleen; Enomoto‐Iwamoto, Motomi
Abstract Articular cartilage is classified as permanent hyaline cartilage and has significant differences in structure, extracelluar matrix components, gene expression profile, and mechanical property from transient hyaline cartilage found in the epiphyseal growth plate. In the process of synovial joint development, articular cartilage originates from the interzone, developing at the edge of the cartilaginous anlagen, and establishes zonal structure over time and supports smooth movement of the synovial joint through life. The cascade actions of key regulators, such as Wnts, GDF5, Erg, and PTHLH, coordinate sequential steps of articular cartilage formation. Articular chondrocytes are restrictedly controlled not to differentiate into a hypertrophic stage by autocrine and paracrine factors and extracellular matrix microenvironment, but retain potential to undergo hypertrophy. The basal calcified zone of articular cartilage is connected with subchondral bone, but not invaded by blood vessels nor replaced by bone, which is highly contrasted with the growth plate. Articular cartilage has limited regenerative capacity, but likely possesses and potentially uses intrinsic stem cell source in the superficial layer, Ranvier's groove, the intra‐articular tissues such as synovium and fat pad, and marrow below the subchondral bone. Considering the biological views on articular cartilage, several important points are raised for regeneration of articular cartilage. We should evaluate the nature of regenerated cartilage as permanent hyaline cartilage and not just hyaline cartilage. We should study how a hypertrophic phenotype of transplanted cells can be lastingly suppressed in regenerating tissue. Furthermore, we should develop the methods and reagents to activate recruitment of intrinsic stem/progenitor cells into the damaged site. Birth Defects Research (Part C) 99:192–202, 2013. © 2013 Wiley Periodicals, Inc.